Synthesis of N-oleyl O-sulfate chitosan from methyl oleate with O-sulfate chitosan as edible film material. (April 2018) - Daniel,; Sihaloho, O; Saleh, C; Magdaleni, A R
Abstract: The research on the synthesis of N-oleyl O-sulfate chitosan through sulfonation reaction on chitosan with ammonium sulfate and followed by amidation reaction using methyl oleate has been done. In this study, chitosan was chemically modified into N-oleyl O-sulfatechitosan as an edible film making material. N-oleyl O-sulfate chitosan was synthesized by reaction between methyl oleate and O-sulfate chitosan. Wherein the depleted chitosan of O-sulfate chitosan into O-sulfate chitosan was obtained by reaction of sulfonation between ammonium sulfate and chitosan aldimine. While chitosan aldimine was obtained through reaction between chitosan with acetaldehyde. The structure of N-oleyl O-sulfate chitosan was characterized by FT-IR analysis which showed vibration uptake of C-H sp 3 group, S=O group, and carbonyl group C=O of the ester. The resulting of N-oleyl O-sulfate chitosan yielded a percentage of 93.52%. Hydrophilic-Lipophilic Balance (HLB) test results gave a value of 6.68. In the toxicity test results of N-oleyl O-sulfate chitosan obtained LC50 value of 3738.4732 ppm. In WVTR (Water Vapor Transmission Rate) test results for chitosan film was 407.625 gram/m 2 /24 hours and N-oleylO-sulfate chitosan film was 201.125 gram/m 2 /24 hours.